Defective insulin receptor signaling in patients with gestational diabetes is related to dysregulated miR-140 which can be improved by naringenin. (November 2020) - Zhao, Chunrong; Zhao, Chunping; Zhao, Honglian
Abstract: Gestational diabetes (GDM) affects about 20 % of pregnancies globally. Defective insulin receptor (IR) signaling has been found in the placenta from patients with GDM, but the underly mechanism is still unclear. In the present study, the mRNA and protein levels of IR-α, insulin receptor substrate 1(IRS-1) and inulin like growth factor 1 receptor (IGF1R) were detected in the placenta tissue samples from 33 GDM patients and 20 healthy controls. Reduced IR-α protein level was observed in both obese and non-obese GDM patients, and decreased IGF1R protein level was found in obese GDM patients. However, the IR-α and IGF1R mRNAs level was not significantly altered in GDM patients. Subsequently, the expression of 10 miRNAs that have the potential targeting IR-α and IGF1R was examined by qRT-PCR in the placenta, and miR-140-3p was found overexpressed. Through dual-luciferase assay and immunoblotting, miR-140-3p was confirmed to suppress IR-α and IGF1R expression via targeting the 3'UTRs. As a treatment candidate, naringenin downregulated miR-140-3p level in trophoblasts and endothelial cells. Meanwhile, IR-α and IGF1R expression was upregulated by naringenin, and the glucose uptake was increased in naringenin treated trophoblasts and endothelial cells. Finally, naringenin upregulated cell viability, migration capacity of HTR-8/SVneo and HUVEC cells, and increased HUVEC cells angiogenesis in high glucose condition. In conclusion, miR-140-3p overexpression contributes to the defective placental IR signaling in patients with GDM. Naringenin treatment protects trophoblasts and endothelial cells from the harmful high glucose environment which have the potential for GDM treatment.